Measuring Managers' Minds: A Critical Reply to Robey and Taggart - Schweiger, David M. (Academy of Management Review, 1983)
Recent interest in studying “managerial cognitive styles” has led to the development and use of a variety of instruments. This paper discusses the importance of instrument description, classification, and evaluation by taking issue with several points made by Robey and Taggart (1981) in a recent issue of the Academy of Management Review. Recommendations also are made concerning those criteria that are critical in the development and/for evaluation of cognitive style instruments.